Visible photoluminescence from Si ion-beam-mixed SiO2/Si/SiO2 layers deposited by e-beam evaporation - Son, JH; Kim, HB; Whang, CN; Sung, MC; Jeong, K; Im, S; Chae, KH (ELSEVIER SCIENCE BV, 2004)
The SiO2/Si (3 nm)/SiO2 layers were deposited by e-beam evaporation, and ion-beam-mixing was performed with 1.5 x 10(16) ions/cm(2) of 55 keV at room temperature. The sample deposited by e-beam evaporation needs the pre-annealing before ion-beam-mixing as well as the post-annealing after ion-beam-mixing to obtain the nanocrystal-related photoluminescence, compared with the study of the sample deposited by ion beam sputtering which was not required the pre-annealing before ion-beam-mixing to obtain visible red photoluminescence. The pre-annealing effect on the photoluminescence of Si ion-beam-mixed SiO2/Si (3 nm)/SiO2 layer will be discussed. (C) 2003 Elsevier B.V. All rights reserved.
Keywords: IMPLANTED SIO2; LUMINESCENCE; TEMPERATURE